The implementation of inquiry based learning in teaching speaking to narrative text by using fairy tale for the eighth grade students of SMPN 2 Jiwan Madiun - Eka Rifael Dipriyansyah (English Teaching Journal : A Journal of English Literature, Language and Education, 2017)
There are four skills in English, namely listening, speaking, reading, and writing. Speaking is the main skill compared to others, because in the process of teaching and learning English teachers and students need a good communication to do speaking activities in expressing their ideas. One method and media for teaching speaking is Inquiry Based Learning used in teaching speaking to narrative text by using fairy tale. The purpose of this study is to describe how to use and the advantages of the shortcomings of Inquiry Based Learning in teaching narrative text by using fairy tale. The strengths of this study is making students feel comfortable, not bored, happy, and building students for self-confidence, increasing students 'ability to analyze sources, motivating students to practice speaking and increasing students' ability to cooperate. The disadvantages are the students who are passive and still dependent on their smart friends, and during the presentation students get problems in composing sentences because of their limited vocabulary. Inquiry Based Learning in teaching speaking to narrative text by using fairy tale can help teachers and students in the learning process, especially in speaking.